Analysis of debris flow characteristics through database construction in korea - yune, Chan-Young; kim, Kyung-Suk; yoo, Na-Jae; Seo, Heung-Seok; jun, Kyoung-Jea (Italian journal of engineering geology and environment, 2011)
In recent years in Korea, Typhoon Rusa (2002), Typhoon Maemi (2003), and the localized extreme rainfall followed by Typhoon Ewiniar in 2006 devastated residential areas, roads, and agricultural lands in Gangwon province where 90% of the area is in mountainous regions. Most of the economic losses and casualties were concentrated in the area near the mountain valleys and creeks due to the floods and debris flows. In this study, DATABASE, which includes a total 153 debris flow events in the Gangwon area, was created by collecting the hazard records and eld investigations of existing debris flow sites. Based on these data, we analyzed geomorphic characteristics of the initiation zone, the initiation and transportation mechanism, and the threshold of rainfall for an early warning system. Analysis results showed the potential for further use of the DATABASE in the development of hazard mapping to predict debris-flow susceptible areas and the assessment of hazard severity in those areas.